Northern natural resources research provides solutions for the green transition – outlook for open strategic autonomy - Kohl, Johanna; Asikainen, Antti; Tolvanen, Anne; Kurttila, Mikko; Viitala, Sirja; Lehto, Jani; Kallasvuo, Meri; Thessler, Sirpa; Kaukovirta, Anu; Kettle, John; Buchert, Johanna (Natural Resources Institute Finland (Luke), 2023)
What if Northern Europe plays a bigger role as a knowledge provider on the sustainable use of natural resources in the future?
Keywords: natural resources; sustainable use; Northern Europe